Virtual Guidance Ultrasound: A New Instructional Concept for Untrained Scanners. Issue 2 (June 2013) - Caine, Timothy L.; Martin, David S.; Matz, Timothy; Lee, Stuart M. C.; Stenger, Michael B.; Platts, Steven H.
Successful acquisition of high-quality ultrasound images for medical diagnoses and scientific research entails several years of intensive training. This time commitment, combined with training requirements for space flight operations, precludes astronauts from proficiently conducting ultrasound examinations without assistance. Therefore, experts in the Johnson Space Center Cardiovascular Laboratory developed a technique called Remote Guidance in which astronauts who possess limited ultrasound training before they launch perform ultrasound examinations in space while receiving real-time feedback about ultrasound probe positioning, scanning technique, study protocol, and image quality through two-way, real-time communication with sonographers on the ground. For instances when time and distance make two-way communication impractical, such as during a mission to Mars or an asteroid, we have developed a form of "just-in-time training" called Virtual Guidance that allows astronauts to autonomously obtain diagnostic ultrasound images by viewing ultrasound tutorials using audio-video glasses while simultaneously performing ultrasound scans. We recently conducted two trials in which we demonstrated the ability of untrained scanners to complete carotid artery and ophthalmic examinations using Virtual Guidance as their only form of instruction. Virtual Guidance can be an important training tool to ensure high-quality ultrasound imaging for scientific and medical applications during future space exploration missions and also could be valuable on Earth in remote areas or applications when a trained sonographer is not readily accessible.